Temporal Shifts in Forage Quality: Stage of Maturity, Biomass Yield, Performance Matrix, and Ecosystem Responses - Md. Emran Hossain; Shilpi Islam (International Journal of Biochemistry and Biomolecule Research, 2025)
Forage quality is a key determinant of livestock productivity and environmental sustainability, with its dynamics closely linked to the stage of maturity, biomass yield, and broader ecosystem interactions. This study explores the temporal shifts in forage quality throughout its growth cycle, emphasizing the effects of maturity on nutrient composition, digestibility, and overall biomass yield. The relationship between these factors and their impact on animal performance, including milk yield, growth, and reproductive health, is examined within the context of a performance matrix that integrates nutritional, physiological, and metabolic outcomes. Additionally, the study investigates the broader ecosystem responses, highlighting how maturity stages influence soil health, water retention, and greenhouse gas emissions, alongside other environmental services such as carbon sequestration. The impact of maturity on forage palatability, intake, and digestibility is critically assessed, providing insights into how changes in plant morphology and biochemical composition affect ruminant feed consumption and efficiency. Furthermore, the role of sustainable forage management practices, including optimal harvest timing and soil-plant management, is discussed to enhance both animal productivity and environmental resilience. This review synthesizes current research, identifies knowledge gaps, and offers future directions for advancing forage management strategies aimed at balancing productivity with ecosystem sustainability.
Keywords: Biomass yield; Sustainability; ecosystem responses; forage maturity; livestock performance; plant-animal interactions; temporal shifts